2015 International Conference on Unmanned Aircraft Systems (ICUAS) 2015
DOI: 10.1109/icuas.2015.7152433
|View full text |Cite
|
Sign up to set email alerts
|

Model-free observer for state estimation applied to a quadrotor

Abstract: In this paper, the Nonlinear Model-Free Observer (NMFO) is proposed to estimate the states of the quadrotor vehicle. NMFO is an integrated structure of the Model-Free technique and the nonlinear Thau observer. The Thau observer will accommodate for the nonlinearities in the quadrotor model and MFO will compensate for the un-modeled dynamics, modeling errors, and the system uncertainties.Flight test results have validated the proposed observer performance towards fault-free and actuator fault conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
2
1
1
Order By: Relevance
“…According to the criteria of the squared errors and energies (see Table 6), it can be observed that, the SMO has proven its effectiveness in terms of accuracy and consumed energy compared to the results obtained by the conventional PID. Unlike the obtained results in works [33,34,35,36,37,38,39,40,41,42,43,44], where the initial conditions are zero, the SMO has presented good performance.…”
Section: Results Interpretationcontrasting
confidence: 84%
“…According to the criteria of the squared errors and energies (see Table 6), it can be observed that, the SMO has proven its effectiveness in terms of accuracy and consumed energy compared to the results obtained by the conventional PID. Unlike the obtained results in works [33,34,35,36,37,38,39,40,41,42,43,44], where the initial conditions are zero, the SMO has presented good performance.…”
Section: Results Interpretationcontrasting
confidence: 84%
“…The demand for methodology applications in productive plants and the equipment industry can be observed in the energy, aeronautical, and chemical sectors. Specifically, applications can be found in quadcopters, rocket tracking, aircrafts, space stations and the agro-industry [20]- [22].…”
Section: Introductionmentioning
confidence: 99%
“…During the development of the sliding mode observer, Utkin [15] first used discontinuous switching items. Subsequently, Walcott and Zak [16] used a Lyapunov-based method to construct observers with discontinuous terms, and the Thau observer [17] was designed for nonlinear systems. The sliding mode observer feeds the output estimation error back via a nonlinear switching term, which effectively solves the problem that the state estimation cannot approach the system state due to unknown interference [18], and increases robustness.…”
Section: Introductionmentioning
confidence: 99%